Influência da adesividade agregado-ligante no trincamento por fadiga de misturas asfálticas - Lucas Júnior, Jorge Luiz Oliveira (2018)
The unsatisfactory aggregate-binder adhesiveness can shorten the service life of asphalt pavements due to the action of moisture, it may speeds the appearance of other defects such as fatigue cracking. The objective of this research was to study the influence of adhesiveness upon fatigue cracking of the asphalt coating. The adhesiveness was investigated from the viewpoint of the physicochemical properties of the aggregates with a pure binder and a binder modified by antistripping agent. An additional mixture investigated with the purpose of evaluating the potential use of plastic bags as an adhesiveness improver. A Digital Image Processing method was developed to make the result of the traditional adhesion test quantitative. The effect of moisture was investigated by the Moisture Induced-Damage test and by the Asphalt Bond Strength pullout test. The shape properties of the aggregates were measured in the Aggregate Image Measurement System. The stiffness characterization was performed using the Axial Compression Dynamic Modulus test and the 2S2P1D model was used for linear viscoelastic modeling. The fatigue of the asphalt mixtures was investigated under a Uniaxial Tension/Compression Cyclic test using the S-VECD protocol. Angularity, texture and porosity of the aggregates not show good correlations with the adhesiveness. On the other hand, iron and calcium oxide content of the aggregates showed good correlations with the adhesiveness, as well as the result of the induced moisture damage. Plastic bags provided better adhesion and moisture damage results when compared to control mixtures. The pullout test results showed that the antistripping produced better response than the pure binder in samples conditioned to moisture for 12 h. As for the characterization of stiffness the pure binder mixtures showed higher values of dynamic modulus |E*| at lower temperatures, while at medium and high temperatures the antistripping produced an increase in |E*| of the analyzed mixtures. The fatigue curves showed that for the same condition of accumulated damage, the integrity of the material remained higher in the mixtures with a specific aggregate in comparison to other and with pure binder comparison the antistripping analyzed. Fatigue simulation showed that the mixtures with better adhesiveness had a longer fatigue life, with the conclusion that the adhesion improver had a positive impact on the fatigue life of the asphalt mixtures analyzed.